2021
DOI: 10.2147/cmar.s304981
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Pseudopapillary Neoplasm of the Pancreas: A 63-Case Analysis of Clinicopathologic and Immunohistochemical Features and Risk Factors of Malignancy

Abstract: Purpose Solid-pseudopapillary neoplasm (SPN) of the pancreas, a rare tumor, has low malignant potential. However, some patients develop metastasis and recurrence after resection, with aggressive biological behaviors. This study aimed to explore the features and risk factors associated with the aggressive biological behaviors of SPNs. Patients and Methods We retrospectively analyzed the clinicopathological and long-term follow-up data of 63 patients diagnosed with SPN at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…Peripheral tissue invasion was rare observed. Some previous studies concluded that lymph node metastasis and positive margin status may be risk factors for poor prognosis of SPN (34,35). However, this relationship was not identified in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…Peripheral tissue invasion was rare observed. Some previous studies concluded that lymph node metastasis and positive margin status may be risk factors for poor prognosis of SPN (34,35). However, this relationship was not identified in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…The main risk factors were large tumor size, lymphovascular invasion, positive margin status, Ki-67 index and synchronous metastasis[ 31 , 32 ]. However, the influence of these factors on the OS rate was not concluded[ 28 , 33 ]. As the overall prognosis is favorable for SPNs, the factors that worsen the OS rate should be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth emphasizing that malignant behaviour cannot be predicted by vascular invasion, perineural invasion, and invasion of adjacent structures in these tumours[ 2 ]. However, it has been suggested that tumours with an undifferentiated carcinoma component have a dismal outcome[ 19 ], and large tumour size, high proliferation index, and lymph node metastasis may be risk factors for a poor prognosis[ 38 ].…”
Section: Prognosismentioning
confidence: 99%